2015
DOI: 10.1016/j.molcel.2015.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Krimper Enforces an Antisense Bias on piRNA Pools by Binding AGO3 in the Drosophila Germline

Abstract: Piwi-interacting RNAs (piRNAs) suppress transposon activity in animal germ cells. In the Drosophila ovary, primary Aubergine (Aub)-bound antisense piRNAs initiate the ping-pong cycle to produce secondary AGO3-bound sense piRNAs. This increases the number of secondary Aub-bound antisense piRNAs that can act to destroy transposon mRNAs. Here we show that Krimper (Krimp), a Tudor-domain protein, directly interacts with piRNA-free AGO3 to promote symmetrical dimethylarginine (sDMA) modification, ensuring sense piR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
104
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(110 citation statements)
references
References 40 publications
(113 reference statements)
6
104
0
Order By: Relevance
“…S1B). Western blotting detected AGO3, Vasa, and Aub in the RNAi-treated cells, while the levels of Piwi, Yb, Armi, and Krimper (Krimp) (Saito et al 2009;Iwasaki et al 2015;Sato et al 2015) remained unchanged (Supplemental Fig. S1C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S1B). Western blotting detected AGO3, Vasa, and Aub in the RNAi-treated cells, while the levels of Piwi, Yb, Armi, and Krimper (Krimp) (Saito et al 2009;Iwasaki et al 2015;Sato et al 2015) remained unchanged (Supplemental Fig. S1C).…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that both Myc-Aub and Myc-AGO3 exogenously expressed in OSCs by transfection are loaded with primary piRNAs, including flam-piRNAs and tj-piRNAs, which are normally loaded onto endogenous Piwi (Olivieri et al 2012;Sato et al 2015). This emphasized the compatibility of AGO3 with primary piRNA loading.…”
Section: Loss Of L(3)mbt Activates the Ping-pong Cycle In Oscsmentioning
confidence: 96%
See 1 more Smart Citation
“…Nuage (which means "cloud" in French) is a conserved perinuclear structure present at the cytoplasmic face of the nuclear envelope in germline cells (Eddy 1975). Interestingly, in Drosophila, many of the nuage proteins have been involved in the production of piRNAs, such as DEAD-box RNA helicases like Vasa (Liang et al 1994), PIWI family proteins Aub and Ago3 (Harris and Macdonald 2001;Brennecke et al 2007;Gunawardane et al 2007), and many Tudor domain proteins such as Krimper (Krimp) (Lim and Kai 2007;Sato et al 2015) and Qin/Kumo Anand and Kai 2012). Thus, nuage was proposed as the potential site for a ping-pong amplification loop in the germline.…”
Section: Introductionmentioning
confidence: 99%
“…22 At our growing conditions aub QC42 is not completely vital, only few escapers survive; as a consequence we and other groups routinely used the aub HN2 /aub QC42 transheterozygotes, in order to analyze aub "loss of function." 3,[23][24][25] For the above reasons, we decided to produce novel and null aub alleles by mobilizing the P element transposon present in the P{lacW} aub sting allele, also known as aub sting . P-element mutagenesis is a convenient method to obtain knock-out mutants.…”
Section: Introductionmentioning
confidence: 99%